PENGARUH LEVERAGE, LIKUIDITAS DAN UKURAN PERUSAHAAN TERHADAP PROFITABILITAS PADA BNI SYARIAH DI INDONESIA PERIODE 2015-2017 - Riska Mailinda; Azharsyah Ibrahim; Zaida Rizqi Zainul (Departemen Manajemen, 2018)
Abstract: This study was conducted to determine the effect of leverage, liquidity, and firm size on profitability in BNI Syariah in Indonesia. Data is obtained from BNI Syariah's monthly financial statements in Indonesia. Profitability is the ability of a company to generate profits in a certain period of sales, total assets and capital. own. The purpose of this study is to analyze the influence of leverage, liquidity, and firm size on profitability in BNI Syariah in Indonesia for the period 2015-2017 both partially and simultaneously. The method used in the research is quantitative and the variables used are leverage, liquidity, and size of the company. The data analysis used is multiple linear regression analysis with the help of SPSS version 22. The results of the study partially with the t-test show that the firm size variable has a positive effect and not significant to BNI Syariah profitability with a value of 0.34 0.05. While the results of the F test (simultaneous) variable size of the company have a significant effect on the profitability of BNI Syariah with a value of 0.02 0.05 and F table (3,434 2,92).Keywords: Leverage, Liquidity, Firm Size, Profitability